FEAR OF READING AND WRITING - Hincapié García, Alexánder; Hincapié García, Alexánder; Hincapié García, Alexánder (Corporación Universitaria Americana, 2022)
A few days ago I attended a meeting of university professors. In it, the conditions for the development of the assigned semester courses were updated. the conditions for the development of the assigned semester courses were updated. A coordinator of the program from which the meeting is being held, specifies its characterization of the students enrolled in the courses. Perhaps she would not say characterization, but rather cartographic fold or something more expressive and sophisticated. At what she points out is that students read little and write less. Qualities that she explains by noting that 'we come from cultures of orality' and that 'our horizons are more narrative than written'. our horizons are more narrative than written'. For this reason, he suggests that courses should not their foundation in writing and, much less, in forcing students to write. to write. What the coordinator indicates is that we have to implement other ways of developing our courses and classes. other ways of developing our courses and classes. In the end, she seems to be relieving us of our tasks as teachers, after all. our tasks as teachers, after all, the students can't read and write and don't want to! and write and they don't want to! As you can imagine, if you judge our time well, the teachers attending the teachers attending the meeting say very little, and those who do say something seem to share the coordinator's those who do say something seem to share the coordinator's criteria. In general, they are all are all eager for new didactic alternatives to replace the outdated traditional education. traditional education. Writing is somewhat obsolete when confronted with the promise of a renewed educational paradise. There is no defense of the need for teachers and students to write! teachers and students to write!